2005
DOI: 10.1007/s11240-004-8153-9
|View full text |Cite
|
Sign up to set email alerts
|

A comparative histological study between normal and fasciated shoots of Prunus avium generated in vitro

Abstract: A combination of Murashige and Skoog's medium and N 6 -benzyladenine (BA) at various concentrations (0, 0.1, 0.25, 0.5, 0.75, 1.0, 1.25 and 1.5 mg l )1 ) was supplied to shoot tips from root cuttings of a 50-yearold wild-cherry tree (Prunus avium). The concentration of BA in the growing medium was a determining factor with respect to the number of proliferated shoots per explant in vitro. Normal and fasciated shoots were generated when BA was present at 0.5, 0.75, 1.0 and 1.25 mg l )1 in the medium and the mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…Sections were counter-stained with 0Á5 % (v/v) Eosin Y (Sigma) in 100 % ethanol. Sections were then treated with 1:1 xylene:absolute ethanol, followed by 100 % xylene at room temperature for 3 min, mounted in Eukitt and dried in a 37 C oven for a minimum of 2 d (Kitin et al, 2005). The stained sections were viewed using a Zeiss Axio Imager M1 compound microscope with brightfield (BF) and differential interference contrast (DIC) optics/lighting capabilities.…”
Section: Light Microscopymentioning
confidence: 99%
“…Sections were counter-stained with 0Á5 % (v/v) Eosin Y (Sigma) in 100 % ethanol. Sections were then treated with 1:1 xylene:absolute ethanol, followed by 100 % xylene at room temperature for 3 min, mounted in Eukitt and dried in a 37 C oven for a minimum of 2 d (Kitin et al, 2005). The stained sections were viewed using a Zeiss Axio Imager M1 compound microscope with brightfield (BF) and differential interference contrast (DIC) optics/lighting capabilities.…”
Section: Light Microscopymentioning
confidence: 99%
“…Previous reports demonstrated that exogenously applied cytokinins induced fasciation in Kalanchoe blossfeldiana (Varga et al 1988), B. pendula (Iliev 1996), Mammillaria elongata (Papafotiou et al 2001), and P. avium (Kitin et al 2005). Also, it has been reported that fasciation in cotton is conditioned by GA 3 and genotype (Nadjimov et al 1999).…”
Section: Hormonal Content In Symptomless Versus Fasciated Tissuesmentioning
confidence: 94%
“…Similarly, fasciation in pea is characterized by abnormal enlargement of the stem apical meristem leading to distortions in shoot structure (Sinjushin & Gostimsky 2006. Fasciated shoots of Betula pendula induced in vitro as well as Prunus avium and Fraxinus excelsior formed flattened stems with densely arranged lanceolate leaves that were dramatically increased in size (Kitin et al 2005;Mitras et al 2009;Iliev & Kitin 2011). …”
Section: Morphological Featuresmentioning
confidence: 99%
“…Enlarged SAMs were observed in tissue culture in the presence of high cytokinin concentrations (Brossard 1976;Iliev and Tomita 2003;Iliev et al , 2011Kitin et al 2005). After cytokinin treatments, calli surrounded with continuous meristematic bands that formed enlarged SAMs were observed.…”
Section: Altered Growth and Morphology Of Fasciated Shootsmentioning
confidence: 98%